Excess Volumes of Mixing for Binary Mixtures of Diethyl Ether with Toluene, o-, m- and p-Xylenes - Gupta, A.K.; Yadav, C.K. (Asian Journal of Chemistry, 2010)
Excess volumes of mixing (VE) for binary mixtures of diethyl ether with toluene, o-, m- and p-xylene as a function of composition and temperature, have been determined dilatometrically. VE values for mixtures have been found to be negative in sign and dependent on temperature. The measurements have been carried out at temperature 283.15 K, 293.15 K and 303.15 K.